+0  
 
0
53
1
avatar

 I don't know how to do this. I keep getting the wrong answer.

 Mar 30, 2021

Best Answer 

 #1
avatar+527 
+1

4 x (4 + 5) = (x - 2)(x + 4 + x - 2)

4 x 9 = (x - 2)(2x + 2)

36 = 2x2 - 2x - 4

x2 - x - 2 = 18

x2 - x - 20 = 0

(x - 5)(x + 4) = 0

x = 5

x = -4 (can't be negative distance)

 Mar 30, 2021
 #1
avatar+527 
+1
Best Answer

4 x (4 + 5) = (x - 2)(x + 4 + x - 2)

4 x 9 = (x - 2)(2x + 2)

36 = 2x2 - 2x - 4

x2 - x - 2 = 18

x2 - x - 20 = 0

(x - 5)(x + 4) = 0

x = 5

x = -4 (can't be negative distance)

Logarhythm Mar 30, 2021

25 Online Users

avatar
avatar
avatar
avatar
avatar
avatar